Correlation between Blood Pressure and vascular complications after coronary artery angiography - Golnoosh Benvan; Mitra SedghiSabet; Mojgan Baghaei; Zahra Atrkar-e Roshan; Asieh Sedighi (Journal of Holistic Nursing and Midwifery)
Introduction: Post-coronary angiography vascular complications (PCAVC) may cause serious life threats, thus recognition of related factorse is needed to prevente complication